Analysis of Tokopedia X BTS Ad Violations: Time for Indonesia to Shop for 12th Birthday Treats on 17 August 2021 - Chaerani, Adinda; Aziz Pamungkas, Abdul; Dita Pratiwi, Yurika (PT Literasi Nusantara Publisher, 2023)
Advertisements are usually distributed via television, radio, social media, magazines, and often appear on billboards on the street. One of the areas that are currently in great demand is e-business, competing companies use advertising services to promote their products and services. These ads are usually used as a way to make online transactions through the use of new technology. These transactions can be in the form of buying and selling advertisements for products or services through social media, such as Facebook, Twitter, Blogspot, website, Instagram, or other social media. One of the advertisements aired by television in 2021 yesterday was the Tokopedia x BTS advertisement; Indonesia Shopping Time! In December 2021. The joining of BTS as Brand Ambassadors is expected to increase Consumer interest in using Tokopedia more often as a shopping facility. The method used to analyze the article entitled